2019
DOI: 10.1111/iej.13104
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of methods used to sample and analyse periradicular tissue fluid during root canal treatment

Abstract: Aim The primary aim was to identify techniques used to sample and analyse periradicular tissue fluid (PTF) in permanent teeth diagnosed with apical disease during root canal treatment. Secondly, to identify the types of inflammatory mediators studied using this approach. Methodology Data Sources: PubMed, EMBASE, Cochrane Library, Science Direct, Web of Science and OpenGrey. Eligibility Criteria: Clinical studies published until 1 June 2018 which utilized orthograde techniques to sample and analyse PTF were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
(149 reference statements)
1
15
0
Order By: Relevance
“…2015, 2016, 2018, Virdee et al . 2019). Safavi & Rossomando (1991) were the first study to sample PTF to investigate inflammatory mediators sampled through the root canal using a paper point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2015, 2016, 2018, Virdee et al . 2019). Safavi & Rossomando (1991) were the first study to sample PTF to investigate inflammatory mediators sampled through the root canal using a paper point.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in a systematic review, Virdee et al . (2019) reported that although several other methods have been explored, such as direct surgical access, fine needle aspiration and absorption with methylcellulose filter points, paper points remain the most commonly used approach. Traditional methods such as direct surgical access are invasive, technique sensitive, and do not permit longitudinal analyses (Torabinejad et al .…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture, laboratory or animal studies and those concerned with investigating inflammatory mediator activity from within healthy or diseased pulp tissue, and not periradicular tissues, were excluded’ (Virdee et al . ). Example 3c : ‘Three electronic databases (Medline, Embase and PubMed) were searched to identify human studies from 1966 to October 2009 in 5 different languages (English, French, German, Italian and Spanish)’ (Setzer et al . ). Example 3d : ‘A literature search was performed in the MEDLINE and EBSCOhost databases until June 2017 with no language restriction’ (Nagendrababu et al .…”
Section: Explanation and Endodontic Examples Of Items In The Prisma Fmentioning
confidence: 97%
“…Cell culture, laboratory or animal studies and those concerned with investigating inflammatory mediator activity from within healthy or diseased pulp tissue, and not periradicular tissues, were excluded’ (Virdee et al . ).…”
Section: Explanation and Endodontic Examples Of Items In The Prisma Fmentioning
confidence: 97%
“…A recent literature review conducted by our group has revealed the most common approach for sampling and analysing the concentrations of periradicular inflammatory mediators during NSRCT is using paper points and proteomic molecular analysis techniques respectively (Virdee et al 2019). Through in vitro experimentation, our group has optimised the sampling and elution procedure so that the maximum amount of PTF is absorbed onto the paper point, and the maximum amount of cytokine is recovered during elution.…”
Section: Data Collection I) Profile Of Inflammatory Mediatorsmentioning
confidence: 99%